TWO-YEAR MORTALITY PROFILE IN ELDERLY WITH FRAILTY : Observational Descriptive Study in Elderly Health Community in Surabaya, Indonesia - Faizah, Ummi Ziyadatul; Widajanti, Novira; Ichwani, Jusri (Journal of Community Medicine and Public Health Research, 2022)
Indonesia in the next few years will face problems related to the increasing population of the elderly. Frailty becomes one of the most common health problems in the elderly. The prevalence of frailty in the Indonesian elderly range from 17% to 36.5%. Frailty raises the risk of death and health care costs, as well as functional disability, hospitalization, and fall risk. This was an observational descriptive study conducted in the elderly health community in Surabaya. This study aimed to determine the proportion and describe the associated factors of 2-year mortality in the elderly with frailty, so it can help determine appropriate preventive and intervention ways to prevent mortality and increase the quality of life in the elderly. There were 113 subjects. Most of the subjects had elementary school grade, married, had an income of less than 1.5 million rupiah/month, financially dependent, regularly exercised, did not use walking aids, and had no history of falls in the last year. The mortality rate within 2 years was 8.8% with the characteristics of older than 70 years old, had sarcopenia, decreased functional status, were at risk of malnutrition, CIRS score > 5, moderate cognitive impairment, probably depression, and had components of exhaustion, slowness, and low physical activity based on the CHS Frailty